TACTICAL MANAGEMENT OF UNEXPECTED CIRRHOSIS IN BARIATRIC SURGERY (International Conference on Modern Science and Scientific Studies, 2025)
This retrospective analysis of 629 consecutive laparoscopic bariatric surgery patients (2023-2024) evaluated management strategies for incidentally discovered liver cirrhosis. Despite standard preoperative screening, 39 patients (6.2%) presented with unexpected intraoperative cirrhosis confirmed by biopsy. Surgical modification was required in 30.8% of cases, including procedure conversions and abandonment. While 69.2% proceeded with technical modifications, complications occurred in 10.2% with one mortality (2.5%). Twelve-month follow-up revealed significant improvements in liver stiffness (18.7 to 12.3 kPa, p